2007
DOI: 10.29173/slw6847
|View full text |Cite
|
Sign up to set email alerts
|

Dispositions in the twenty-first century school library profession

Abstract: Within the school library profession there is an emerging focus on dispositions, defined as "a tendency to exhibit frequently, consciously, and voluntarily a pattern of behavior that is directed to a broad goal" (Katz, 1993). Directed focus groups of practicing school librarians were asked to articulate their vision for school libraries of the future. Data from these groups informed development of six dispositional continua to guide both school library education and school librarianship in the 21stcentury.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Each disposition in the continua is presented with representative quotations from the participants' interviews to explore what dispositions these TL leaders bring to and demonstrate in their leadership roles. Kimmel et al's (2012) first disposition, From Expertise to Advocacy, was highlighted by several of the participants in this study. Advocacy took many forms, including creating presentations and booklets, as well as daily informal conversations with school leaders to highlight the role of the teacher-librarian and the value a TL brings to the school.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Each disposition in the continua is presented with representative quotations from the participants' interviews to explore what dispositions these TL leaders bring to and demonstrate in their leadership roles. Kimmel et al's (2012) first disposition, From Expertise to Advocacy, was highlighted by several of the participants in this study. Advocacy took many forms, including creating presentations and booklets, as well as daily informal conversations with school leaders to highlight the role of the teacher-librarian and the value a TL brings to the school.…”
Section: Resultsmentioning
confidence: 85%
“…This paper specifically addresses the second question and presents findings from six in-depth interviews with teacher-librarian leaders (TL Leaders) who are currently working in a variety of formal leadership roles. Findings are organized and presented based on the leadership dispositions identified by Kimmel et al (2012) in their Dispositional Continua. Each disposition in the continua is presented with representative quotations from the participants' interviews to explore what dispositions these TL leaders bring to and demonstrate in their leadership roles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are change agents, risk takers, and invested in school reform (Shannon, 2002). Kimmel et al (2012) identified dispositions of TL leadership which includes embracing diversity, willing to change, being proactive, and curious. Shannon's (2002) literature review on the competencies of TLs, found that strong interpersonal and communications skills are foundational to all aspects school library work.…”
Section: Review Of Literaturementioning
confidence: 99%